Principles of Antibiotic Management of Community-Acquired Pneumonia - Bender, Michael T.; Niederman, Michael S. (Seminars in Respiratory and Critical Care Medicine, 2016)
Community-acquired pneumonia (CAP) encompasses a broad spectrum of disease severity and may require outpatient, inpatient, or intensive care management. Successful treatment hinges on expedient delivery of appropriate antibiotic therapy tailored to both the likely offending pathogens and the severity of disease. This review summarizes key principles in starting treatment and provides recommended empiric therapy regimens for each site of care. In addition, we discuss the antimicrobial and anti-inflammatory role macrolides play in CAP, as well as specific information for managing individual CAP pathogens such as community-acquired methicillin-resistant Staphylococcus aureus and drug-resistant Streptococcus pneumoniae. We also examine several novel antibiotics being developed for CAP and review the evidence guiding duration of therapy and current best practices for the transition of hospitalized patients from intravenous antibiotics to oral therapy.
Keywords: pneumonia; initiation of antibiotics; duration of antibiotics; macrolides; clinical outcomes